Design of Zero Voltage Switching Boost DC-DC Converter Using Bond Graph Model - Shaik Hussain Vali; R Kiranmayi (Politeknik Elektronika Negeri Surabaya (PENS), 2020)
The research in power supply design is moving towards improving efficiency by reducing losses. Another aspect of research in power converters is its modeling as it involves multiple domains such as electrical, mechanical, magnetic...etc. bond graph modeling is suitable for the multi domain systems. Here, a zero voltage switching boost converter is designed using its bond graph model. The bond graph simulated results which are done in MATLAB/SIMULINK are matched with the experimental results. The efficiency of the ZVS boost converter is calculated and is compared with the efficiency of conventional pulse width modulated (PWM) boost converter.